Gender Differences In Letter Shape Recognition To 4-5 Year Old Children In Yogyakarta, Indonesia - Munawarah, (Jurnal Serambi Ilmu, 2024)
Learning in Kindergarten aims to develop some abilities possessed by children including oral communication ability, literacy and reading ability, listening ability and comprehension of command, writing ability, and ability to use literature. The gender gap remains ongoing issue in Indonesia. This paper presents evidence of gender differences in learning in differences in letter shape recognition to 4-5 year old children in which 30 children from two schools participated. This study using Quantitative research methods in comparative research. The result of this study indicates there are a difference between boys and girls aged 4-5 years in terms of recognizing and interpreting the symbols of letters in Yogyakarta, Indonesia.